THE EFFECT OF ENTREPRENEURSHIP AND INNOVATION TOWARDS BUSINESS SUCCESS IN BREAD INDUSTRY IN SUB-DISTRICT EAST BATURAJA OGAN KOMERING ULU DISTRICT - Dewi, Rosmala (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
This study discusses the influence of entrepreneurial spirit and innovation on business success in the bakery industry in the form of questionnaires totaling of 18 for X variables and 10 statements for variable Y which are scored based on Likert scale and distributed to 20 respondents. The analiysis is performed quantitatively using multiple linier regression to show whether there is an influence of entrepreneurial spirit (Xl) and innovation (X2) on business success (Y), hypothesis testing is done by partial and simultaneous testing. Based on the result of the analysis, it can be concluded: first, there is a positive and significant influence between entrepreneurial spirit (X1) and innovation (X2) on the business success (Y) in the bakery industry in Baturaja sub-districts, Ogan Komering Ulu Regency; second, that the analysis results The coefficient of determination (R square) shows that that there is a positive and significant influence between entrepreneurial spirit (Xl) and innovation (X2) on business success (Y) of 0,657 or 65,7% while the rest remaining 34,3% is influenced by other factors that are not included in this study. like motivation and education.